2012
DOI: 10.2478/v10182-012-0012-0
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid and Organic Acid Content in Rose Hips (Rosa L., Sect. Caninae Dc. Em. Christ.)

Abstract: We determined the level of flavonoids, citric acid and ascorbic acid in hips of rose species from the Caninae section occurring in Poland. We performed phytochemical analyses of 75 samples representing 11 species: Rosa agrestis Savi, R. canina L., R. dumalis Bechst., R. glauca Pourret, R. inodora Fries, R. jundzillii Besser, R. rubiginosa L., R. sherardii Davies, R. tomentosa Sm., R. villosa L. and R. zalana Wiesb. Flavonoid content was determined spectrophotometrically, and organic acid concentrations by HPLC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 43 publications
4
47
1
4
Order By: Relevance
“…The trend of variation of the organic acids in the plants studied was malic acid > citric acid > succinic acid > fumaric acid. Adamczak et al (2012) reported citric acid contents in different species of rose, viz., Rosa agrestis (1.08 mg/g dw), R. tnodora (1.95 mg/g dw), and R. jundzillu (2.90 mg/g dw). Roriz et al (2014) reported malic acid contents in Pterospartum tridentatum (3.23 mg/g dw), Cymbopogon citratus (2.23 mg/g dw), and Gomphrena globosa (12.33 mg/g dw).…”
Section: Resultsmentioning
confidence: 99%
“…The trend of variation of the organic acids in the plants studied was malic acid > citric acid > succinic acid > fumaric acid. Adamczak et al (2012) reported citric acid contents in different species of rose, viz., Rosa agrestis (1.08 mg/g dw), R. tnodora (1.95 mg/g dw), and R. jundzillu (2.90 mg/g dw). Roriz et al (2014) reported malic acid contents in Pterospartum tridentatum (3.23 mg/g dw), Cymbopogon citratus (2.23 mg/g dw), and Gomphrena globosa (12.33 mg/g dw).…”
Section: Resultsmentioning
confidence: 99%
“…Adamczak i wsp. [1] oznaczyli zawartość witaminy C w 75 próbkach 11 odmian róż rosnących na terenie Polski. Największą zawartością witaminy C charakteryzowały się owoce Rosa villosa (2,25 g/100 g s.m.…”
Section: Wyniki I Dyskusjaunclassified
“…), a najmniejszą -Rosa canina (0,51 g/100 g s.m.). Autorzy [1,3,12,28] wskazują, że różnice w zawartości witaminy C w badanych owocach róż mogą wynikać z cech gatunku, czasu dojrzewania, dojrzałości, warunków agroklimatycznych, jednak wiele badań wskazuje, że zawartość tej witaminy w owocach róż jest cechą bardzo zmienną, nawet w obrębie tego samego gatunku. Liczne dane literaturowe dotyczące róż owocowych wskazują, że nasiona traktowane są często jako materiał odpadowy [4,9,21,24].…”
Section: Wyniki I Dyskusjaunclassified
See 2 more Smart Citations